2011
DOI: 10.1038/gt.2011.177
|View full text |Cite
|
Sign up to set email alerts
|

Cross-presentation of tumour antigens by human induced pluripotent stem cell-derived CD141+XCR1+ dendritic cells

Abstract: Monocyte-derived dendritic cells (moDC) have been widely used in cancer immunotherapy but show significant donor-to-donor variability and low capacity for the cross-presentation of tumour-associated antigens (TAA) to CD8 þ T cells, greatly limiting the success of this approach. Given recent developments in induced pluripotency and the relative ease with which induced pluripotent stem (iPS) cell lines may be generated from individuals, we have succeeded in differentiating dendritic cells (DC) from human leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 30 publications
(35 reference statements)
2
53
0
Order By: Relevance
“…S1A). The pMCs were treated with GM-CSF and IL4 (days [23][24]. After 3 days of culture, the pMCs differentiated into DC-like cells (pMC-DC; days [26][27].…”
Section: Generation Of Pmcs From Mouse Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1A). The pMCs were treated with GM-CSF and IL4 (days [23][24]. After 3 days of culture, the pMCs differentiated into DC-like cells (pMC-DC; days [26][27].…”
Section: Generation Of Pmcs From Mouse Pscsmentioning
confidence: 99%
“…Previous studies have established methods of generating DCs from PSCs, and demonstrated the utility of PSC-derived DCs in cancer immunotherapy (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, generating a large number of DCs from ESCs or iPSCs has required a scaling-up of the initial volume of undifferentiated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to generate a potentially unlimited source of DCs from iPS cells offers the possibility of harnessing their capacity for cross-priming cytotoxic T lymphocytes inducing a tumor-specific immune response. 66 …”
Section: Transplantation Of Differentiated Blood Cell Typesmentioning
confidence: 99%
“…Despite the promising results, isolation and in vitro propagation of DCs still represents the most challenging task which also increases the overall costs. This therapeutic limitation of DCs can be overcome by using iPSCs-derived DCs and hence represents the renewable source to broaden the immunotherapeutic applications [46]. Silk et al have successfully generated CD141 + XCR1 + DCs from iPSCs using combination of stem cell factor (SCF), granulocyte macrophage-colony stimulating factor (GM-CSF), bone morphogenetic protein-4 (BMP4) and vascular endothelial growth factor (VEGF) without the usage of animal products.…”
Section: Ipscs In Cancer Immunotherapymentioning
confidence: 99%